The Influence Of Entrpreneuriaal Knowledge, Social Skills And Self-Efficacy In Commitment To Running A Bussiness In Covid-19 Pandemic Period - Gita Novia Sahara; Tuty Sariwulan; Sri Indah Nikensari (Journal of Comprehensive Science (JCS), 2022)
This is a study on the influence of entrepreneurial knowledge, social skills, and self-efficacy on commitment to running a business during the COVID-19 pandemic (case study of independent entrepreneurial students at the Jakarta State University). This study aims to determine the influence exerted by entrepreneurial knowledge, social skills on entrepreneurial commitment directly or through influencing factors, namely self-efficacy. In particular, this study uses the classical assumption test, requirements analysis test and path analysis. Empirical results show entrepreneurial knowledge, social skills and self-efficacy have an effect on entrepreneurial commitment. Further analysis reveals that entrepreneurial knowledge and social skills affect entrepreneurial commitment through self-efficacy. The regression equation means that if the Entrepreneurial Knowledge variable increases by one unit, the Entrepreneurial Commitment will increase by 0.205 or by 20.5%. Furthermore, if Social Skills are increased by one unit, then Entrepreneurial Commitment will increase by 0.465 or 46.5%. Furthermore, if Self-efficacy increases by one unit, then Entrepreneurial Commitment will increase by 0.258 or by 25.8%. The regression equation means that if the Entrepreneurial Knowledge variable increases by one unit, then Self-efficacy will increase by 0.647 or 64.7%. Furthermore, if Social Skills increase by one unit, then Self-efficacy will increase by 0.306 or by 30.6%.